KAJIAN DAMPAK EKONOMI KEBERADAAN HYPERMARKET TERHADAP RITEL/PASAR TRADISIONAL - Ninuk Rahayuningrum; Tjahya Widayanti (Trade Analysis and Development Agency, Ministry of Trade of Republic of Indonesia, 2008)
Traditional retail market share tendencies to decline, along with the increasingly growing number of modern retail business and capitalization. Domination of the market amounted to one-third to half of them by modern retail is very prone to bring the potential cost of the economic, social, and political stature. In Indonesia, the market share of traditional markets and business performance declines, while at the same time modern markets has increased. However, quantitatively, not proven the existence of real influence. More traditional markets decline caused by internal factors are real. More traditional markets decline caused by internal factors which resulted in a lack of competitiveness in the field of modern markets, which are related to performance: assets, turnover, turnover of merchandise, and margin rates. The possession of wealth (assets) stagnant. Secondary data analysis suggests that any amount of additional modern market (grocery store) yet are lowering the number of traditional markets (stores or stalls). This shows that the market for modern and traditional markets are equally evolved and are 'complementyary' of each other. Results of the study indicate that the contribution to the GDP of non oil and gas more traditional markets (stores or stalls) compared to modern market (grocery store). However, the opposite happens, the condition that the modern market (supermarket) in the territory of the province, in this case urban, had a greater contribution towards the recipient APBD compared to city or regency. In contrast, the traditional market of non economic advantages from the point of view of macro economic interests, namely the provision of business opportunity selection, provision of employment, output and contributions, although these choices may conflict with the interests of the local Government to improve the acquisition of PAD.